2021
DOI: 10.3390/ijms22031040
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Cytochemical Detection of Polyphosphates Associated with Human Platelets

Abstract: Polyphosphate (polyP) is released from activated platelets and activates the intrinsic coagulation pathway. However, polyP may also be involved in various pathophysiological functions related to platelets. To clarify these functions, we established a cytochemical method to reproducibly visualize polyP in platelets. Platelets obtained from healthy non-smoking donors were suspended in phosphate-buffered saline and quickly immobilized on glass slides using a Cytospin. After fixation and membrane permeabilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…Regarding possible degradation by phosphatases, we did not find that orthovanadate (1 mM) significantly increased polyP values. As a result, the exogenous addition of 0.1% CaCl 2 to the platelets reduced platelet polyP levels in a concentration-dependent manner, and the amount of polyP remaining in the platelets approximately corresponded to the cytochemical visualization data shown in the present and previous studies [17].…”
Section: Optimization and Validation Of The Quantification Protocolsupporting
confidence: 86%
See 3 more Smart Citations
“…Regarding possible degradation by phosphatases, we did not find that orthovanadate (1 mM) significantly increased polyP values. As a result, the exogenous addition of 0.1% CaCl 2 to the platelets reduced platelet polyP levels in a concentration-dependent manner, and the amount of polyP remaining in the platelets approximately corresponded to the cytochemical visualization data shown in the present and previous studies [17].…”
Section: Optimization and Validation Of The Quantification Protocolsupporting
confidence: 86%
“…Growth factors and fibrinogen contained in platelets are major factors involved in tissue regeneration. In a previous study [ 17 ], however, we confirmed that activated platelets secrete polyP along with the growth factors [ 26 ]. If polyP has a potent ability in tissue repair and regeneration [ 10 , 27 ], we expect PCs containing significant amounts of polyP to be applicable for regenerative therapy, as shown previously [ 28 ], and hypothesized that polyP may be utilized as a marker of the quality of PCs, i.e., a marker of their predictable clinical outcomes.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Due to the lack of specific probes, it is difficult to accurately quantify platelet polyP levels in an efficient manner. In previous studies, 17,18 we optimized the previous methods, especially those related to sample preparation and the parameter of light wavelengths in fluorescent determination, for quantification and visualization of platelet polyP using DAPI. Although not completely excluding the possible count of DAPI-bound, non-polyP substances, this method enables rapid quantification of polyP levels without sacrificing recovery or reproducibility.…”
Section: Introductionmentioning
confidence: 99%